Caregivers' experience of the decision-making process for placing a person with dementia into a nursing home: comparing caregivers from Chinese ethnic minority with those from English-speaking backgrounds. (March 2014) - Caldwell, Lauren; Low, Lee-Fay; Brodaty, Henry
ABSTRACT Background: The experience of care transitions for people with dementia from ethnic minority groups has been poorly researched. Few studies have examined the decision to put someone on a waiting list for a nursing home and then actually accept a place. Many nursing homes have long waiting lists, but sometimes offers of a place are declined. Our aims were to investigate the decision-making process for placing a person with dementia on a waiting list for a nursing home, why offers of a place are accepted or declined, and the influence of cultural factors, comparing caregivers from Chinese and English-speaking backgrounds. Methods: Semi-structured interviews with 27 caregivers of people with dementia on waiting lists or living in nursing homes (20 Chinese background and seven English-speaking background) were conducted, with thematic analysis of factors affecting caregivers' decision-making. Results: Caregivers were at different stages of decision-making when they applied for a waiting list – some were ready for placement, others applied "just in case, " and for some there was no waiting time because of an urgent need for placement. Caregivers' decisions were influenced by their emotions and expectations of nursing homes. The decision-making process was similar for both cultural groups, but Chinese caregivers spoke more about their sense of duty, the need for a Chinese specific facility, and declining a place because of family disagreement. Conclusions: Understanding cultural issues, including stereotypes and concerns about nursing homes, and providing better information about admission processes may help caregivers by allaying their anxiety about nursing home placement.